1
y`=[((3x²+5)³)`*(2x-3)-(2x-3)`*(3x²+5)³]/(2x-1)²=
=[3(3x²+5)²*6x*(2x-1)-2(3x²+5)³]/(2x-1)²=2(3x²+5)(18x²-27x-3x²-5)/(2x-1)²=
=2(3x²+5)(15x²-27x-5)/(2x-1)²
2
y`=[tg²(x²+1)]`*[tg(x²+1)]`*(x²+1)`=2tg(x²+1)*1/cos(x²+1)*2x=8x*tg(x²+1)/cos²(x²+1)
3
y`=[(1+cos²x)^1/4]`*(1+cos²x)`=![1/ \sqrt[4]{(1+cos^2x)^3} *2cosx*(-sinx)=-sin2x/ \sqrt[4]{(1+cos^2x)^3} 1/ \sqrt[4]{(1+cos^2x)^3} *2cosx*(-sinx)=-sin2x/ \sqrt[4]{(1+cos^2x)^3}](https://tex.z-dn.net/?f=1%2F+%5Csqrt%5B4%5D%7B%281%2Bcos%5E2x%29%5E3%7D+%2A2cosx%2A%28-sinx%29%3D-sin2x%2F+%5Csqrt%5B4%5D%7B%281%2Bcos%5E2x%29%5E3%7D+)